Neurosurgical and Intensive Care Management of Traumatic Brain Injury - Seule, Martin; Brunner, Thomas; Mack, Alexander; Hildebrandt, Gerhard; Fournier, Jean-Yves (Facial Plastic Surgery, 2015)
Optimal management of patients with traumatic brain injury (TBI) remains a challenge, despite significant improvements in pathophysiologic understanding and treatment strategies in recent decades. Because primary brain injury sustained at the time of trauma is irreversible, the TBI management mainly aims for early detection and treatment of secondary brain injury such as space-occupying intracerebral hematomas and brain edema. Prevention of secondary brain injury requires a high standard of care and understanding of both medical and surgical treatment modalities. This review focuses on practical recommendations for neurosurgical and intensive care management in patients with severe TBI.
Keywords: traumatic brain injury; neurosurgery; neurocritical care